Hymns for the fallen : combat movie music and sound after Vietnam - Decker, Todd R. (University of California Press, 2017)
"This book describes in detail how music and sound function as a constituent part of the prestige combat film's larger work of memorialization in the cultural realm of commercial cinema. As Rikke Schubart and Anne Gjelsvik note, historians must deal with 'the complexity of history, war, heroism, patriotism, memory, and the process of their representation.' Hymns for the Fallen traces an expressive sonic continuity in this 'process of representation' for serious war films. The three elements of the soundtrack--dialogue, sound effects, music--are treated in detail in the chapters which follow, although music proves to be of particular interest"--Provided by publisher.